The Role of Social Support and the Neighborhood Environment on Physical Activity in Low-income, Mexican-American Women in South Texas - Jennifer J. Salinas; Marisol McDaniel; Deborah Parra-Medina (Korean Society for Preventive Medicine, 2018)
Objectives To determine the relationships between physical activity (PA), the neighborhood environment support for PA, and social support for PA among Mexican-American women living in South Texas. The Enlace study was a randomized controlled trial that tested the effectiveness of a promotora-led PA intervention among low-income Mexican origin women (n=614) living in colonias. Methods The dependent measures included accelerometer-measured average moderate to vigorous physical activity (MVPA) and sedentary breaks and the Community Health Activities Model Program for Seniors PA 41-item questionnaire. The independent measures included the Physical Activity and Neighborhood Environment Scale (PANES) and the 13-item Physical Activity Social Support (PASS) scale. Results Enlace participants were on average 40.4 (standard deviation, 10.3) years old, born in Mexico (86.1%), and uninsured (83.1%). Adjusted linear regression results indicated that each 1-point increment in the PANES overall score was associated with 0.050 (p<0.001) unit increase in sedentary break and a −0.043 (p=0.001) unit decrease in sedentary break duration. Both PANES (β=0.296; p=0.002) and PASS scores (β=0.076; p<0.001) were associated with weekly average self-reported MVPA. Interaction effects were observed between PASS scores and accelerometer-measured frequency of sedentary breaks and sedentary time duration. Conclusions The findings of this study indicate that the relationships between PA and built environment and social support are measure-dependent and suggest that reducing sedentary time in this population may require a closer assessment of social support for PA.